Fascism and democracy in the human mind : a bridge between mind and society - Charny, Israel W. (University of Nebraska Press, 2006)
What might you have done if you had been caught up in the Holocaust? In My Lai? In Rwanda? Confronted with acts of violence and evil on scales grand and small, we ask ourselves, baffled, how such horrors can happen-how human beings seemingly like ourselves can commit such atrocities. The answer, I.W. Charny suggests in this important new work, may be found in each one of us, in the different and distinct ways in which we organize our minds. An internationally recognized scholar of the psychology of violence, Charny defines two paradigms of mental organization, the democratic and the fascist, and shows how these systems can determine behavior in intimate relationships, social situations, and events of global significance. With its novel conception of mental health and illness, this book develops new directions for diagnosis and treatment of emotional disorders that are played out in everyday acts of violence against ourselves and others. Fascism and Democracy in the Human Mind also offers much-needed insight into the sources and workings of terrorism and genocide. A sane, radical statement about the guiding principles underlying acts of violence and evil, this book sounds a passionate call for the democratic way of thinking, which recognizes complexity, embraces responsibility, and affirms life.